Association of plasma and cortical amyloid beta is modulated by APOE ε4 status. Issue 1 (28th March 2013) - Swaminathan, Shanker; Risacher, Shannon L.; Yoder, Karmen K.; West, John D.; Shen, Li; Kim, Sungeun; Inlow, Mark; Foroud, Tatiana; Jagust, William J.; Koeppe, Robert A.; Mathis, Chester A.; Shaw, Leslie M.; et al.
Abstract: Background: Apolipoprotein E ( APOE ) ε4 allele's role as a modulator of the relationship between soluble plasma amyloid beta (Aβ) and fibrillar brain Aβ measured by Pittsburgh compound B positron emission tomography ([ 11 C]PiB PET) has not been assessed. Methods: Ninety‐six Alzheimer's Disease Neuroimaging Initiative participants with [ 11 C]PiB scans and plasma Aβ1–40 and Aβ1–42 measurements at the time of PET scanning were included. Regional and voxelwise analyses of [ 11 C]PiB data were used to determine the influence of APOE ε4 allele on association of plasma Aβ1–40, Aβ1–42, and Aβ1–40 /Aβ1–42 with [ 11 C]PiB uptake. Results: In APOE ε4− but not ε4+ participants, positive relationships between plasma Aβ1–40 /Aβ1–42 and [ 11 C]PiB uptake were observed. Modeling the interaction of APOE and plasma Aβ1–40 /Aβ1–42 improved the explained variance in [ 11 C]PiB binding compared with using APOE and plasma Aβ1–40 /Aβ1–42 as separate terms. Conclusions: The results suggest that plasma Aβ is a potential Alzheimer's disease biomarker and highlight the importance of genetic variation in interpretation of plasma Aβ levels.